Can MRI help assess aggressiveness of endometrial cancer?. Issue 9 (September 2018) - Ahmed, M.; Al-Khafaji, J.F.; Class, C.A.; Wei, W.; Ramalingam, P.; Wakkaa, H.; Soliman, P.T.; Frumovitz, M.; Iyer, R.B.; Bhosale, P.R.
Abstract : Aim: To identify potential magnetic resonance imaging (MRI) biomarkers to predict the aggressiveness of endometrial cancer. Materials and methods: Seventy-one patients with endometrial cancer who underwent MRI staging were analysed retrospectively. The signal intensity (SI) of the tumours was assessed on sagittal T2-weighted imaging (WI) and sagittal T1WI sequences). The depth of myometrial invasion, tumour grade and subtype, lymphovascular invasion, and microsatellite stability status were assessed histopathologically, and these findings were compared with MRI findings using logistic regression. The log-rank test was used to assess differences in survival among groups defined by different MRI measurements. Results: Tumours with qualitative higher signal than that of normal myometrium on the late T1WI DCE image sequences were more likely to have lymphovascular space invasion ( p< 0.001). Tumours that had a higher SI tumour ratio (T1 post-contrast arterial/T1 precontrast) had a higher chance of being microsatellite stable (odds ratio 2.36). The SI ratio of the tumour to the myometrium showed that lower T2 tumour/T2 myometrial ratio correlated with ≥50% depth of myometrial invasion as determined by imaging ( p= 0.006). Endometrial tumours showing a SI of >209 on delayed T1WI sequences had longer recurrence-free survival than those with tumours showing a SI ≤209 ( p= 0.014). Tumour subtype and grade were not associated with MRI findings. Conclusion: The SI of endometrial cancer on MRI may be used to predict the aggressiveness of the tumour and microsatellite stability status. Further studies are needed to confirm these findings. Highlights: Ability to predict aggressiveness of the tumour and microsatellite stability status on MRI is proposed. Signal intensity of the tumour may be able to predict survival. MRI may be used as a prognostic indicator in endometrial cancer.